Analysis of robustness of homogeneous systems with time delays using Lyapunov‐Krasovskii functionals. (17th July 2020) - Efimov, D.; Aleksandrov, A.
Summary: This article is devoted to stability analysis of homogeneous time‐delay systems applying the Lyapunov‐Krasovskii theory, and a generic structure of the functional is given that suits for any homogeneous system of nonzero degree (and can also be used for any dynamics admitting a homogeneous approximation). The obtained stability conditions are utilized to evaluate the domain of attraction for the delayed twisting control algorithm.